Circular product design challenges: An exploratory study on critical barriers - Jugend, Daniel [UNESP]; dos Santos, Hugo Henrique [UNESP]; Garrido, Susana; Siqueira, Regiane Máximo [UNESP]; Mesa, Jaime A. (Wiley, 2024)
Despite the recognition that the adoption of the circular economy depends on aligning the new product development process with the principles of circularity, there are still few studies on the barriers to circular product design. This article aims to contribute to this topic by developing an exploratory study to identify and analyze these barriers in the Brazilian context. In addition to a theoretical analysis, the fuzzy analytic hierarchy process was utilized to evaluate the significance of various hindrances and obstacles to circular product design. To gain a better understanding of these barriers, semi-structured interviews were also conducted. Experts in areas such as sustainability, marketing, and R&D from companies that develop products participated in this research. The results of the study reveal that the difficulties supply chains have in providing circular economy-based products and reverse logistics systems are among the main barriers. Challenges such as low consumer valorization of these products and a lack of knowledge and technologies were also identified as relevant. By investigating a set of barriers to circular product design, this study extends knowledge about the difficulties companies face in the transition to circular business models.
Keywords: barriers; circular economy; new product development; product innovation; sustainability; sustainable design